REAL TIME DATA ACQUISITION SYSTEM FOR THE ECP-EPP PARALLEL PORT BASED ON PIC16F877 MICROCONTROLLER - Kalomiros, John A. (International Journal of Computing, 2014)
The design of a simple and low cost 10-bit data acquisition system is presented which makes use of the peripherals of a PIC16F877 microcontroller, interfacing with a personal computer using the extended capabilities of the parallel port. The system is integrated with a visual programming tool based on LabVIEW data acquisition software, which provides design flexibility and real time signal processing capabilities. An optimum assembly code for the PIC microcontroller allows for a free-running mean sampling rate of 100KSps on a Pentium PC running Windows XP OS. This system can be an example of a low cost integrated approach for data acquisition that includes a microcontroller, a personal computer and visual measurement software. The system can be the basis of a A/D interface for many measurement applications and can also be seen as an educational paradigm in itself. An effective and fast DAC solution is also presented in full integration with the microcontroller and the computer parallel port.